ESTIMATION OF SOME GENETIC PRAMETERS IN DURUM WHEAT - & et al., Almajidy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
To estimate genetic parameters and heritability in durum wheat (Triticum turgidum var. durum) genotypes, seventeen genotypes (16 exotic from ICARDA and local variety (Buhooth 7)) were included in this study. This experiment was conducted using a randomized complete block design with three replications at Field Crops Research Station, Abu-Graib, Office of Agricultural Research, during 2011-2012 and 2012-2013. The results revealed significant differences among genotypes for the studied characters at both seasons. The best genetic/environmental variance ratio attained for spike length (11.90) and no. of spikes. m-2 (9.22) in the first season, and grain yield (8.82) then harvest index (4.87) in the second season. High GCV observed for grain yield (15.68), no. of spikes. m-2 (15.18) in the first season, and harvest index (16.89) and grain yield (14.22) in the second season. High heritability estimates associated with high genetic advance for no. of spikes. m-2, in the first season. While, moderate h2bs estimates associated with high GA for same trait in the second season. Expected response to selection ranged from 0.93 to 84.6, also selection index ranged from 1.23 to 106.44 for grain yield and number of spikes. m-2, respectively in the first season also the same pattern was observed for value of second season. Characteristics like no. of spikes. m-2, plant height, no. of grains. Spike-1 and grain weight showed high heritability coupled with high genetic progress. Therefore, these characters should be given top priority during selection breeding in durum wheat.